2020
DOI: 10.1088/1755-1315/492/1/012154
|View full text |Cite
|
Sign up to set email alerts
|

Causes of low pregnancy rates in beef cattle through artificial insemination technology in Soppeng Regency (case study: performance of the 2018 UPSUS SIWAB)

Abstract: The objective of this study was to examine the causes of low pregnancy rate in beef cattle through artificial insemination in the 2018 UPSUS SIWAB program in Soppeng Regency. This type of study was exploratory by involving three informants who were considered to know clearly the causes of low pregnancy rate in beef cattle through artificial insemination in the 2018 UPSUS SIWAB program in Soppeng Regency. The informants were beef cattlle farmers, inseminator, and the staff of the animal livestock services of So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The possession of a mobile device is also a crucial determinant factor that enables AI beneficiaries to receive prompt service from the AI technician when their cows come into heat (Abraha et al, 2020). According to research conducted by Bonewati et al (2020), a minority of farmers in Soppeng Regency showed no intention of getting their cows' pregnancy checked. Farmers have identified a lack of knowledge and awareness regarding the significance of a particular task.…”
Section: Regional Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The possession of a mobile device is also a crucial determinant factor that enables AI beneficiaries to receive prompt service from the AI technician when their cows come into heat (Abraha et al, 2020). According to research conducted by Bonewati et al (2020), a minority of farmers in Soppeng Regency showed no intention of getting their cows' pregnancy checked. Farmers have identified a lack of knowledge and awareness regarding the significance of a particular task.…”
Section: Regional Accessibilitymentioning
confidence: 99%
“…The profitability of a farming enterprise is a crucial factor that motivates farmers to adopt new technologies. If a technology is perceived to be profitable, farmers are more likely to implement it in their farming practices (Bonewati et al, 2020). Profitability is a crucial driver of business success and sustainability, and farmers are no exception to this rule.…”
Section: Farmers' Motivation To Attend the Extensionmentioning
confidence: 99%